PERCEIVED PARENTAL BLAME AND EMOTION REGULATION AS PREDICTORS OF ADULT PSYCHOLOGICAL DISTRESS: DEVELOPMENT AND VALIDATION OF THE PERCEIVED PARENTAL BLAME SCALE - Okan, Nesrullah (Int Inst Advanced Studies Psychotherapy & Applied Mental Health, 2026)
The present study developed and validated the Perceived Parental Blame Scale (PPBS) and examined the underlying psychological mechanisms that connect perceived parental blame experienced during childhood to emotional distress in adulthood. The present study is anchored in attachment theory and emotion regulation frameworks. Its objective is to explore how early perceptions of parental blame may shape long-term emotional functioning and vulnerability to psychological difficulties. Specifically, a mediation model was tested in which difficulties in emotion regulation were hypothesized to explain the relationship between parental blame and adult symptoms of depression, anxiety, and stress. Two independent adult samples were recruited to ensure methodological robustness. The initial sample (N = 308) was utilised to conduct exploratory and confirmatory factor analyses, which substantiated a unidimensional and psychometrically sound factor structure of the PPBS with high internal consistency. The second sample (N = 576) was used for structural equation modelling, which confirmed that perceived parental blame significantly predicted elevated levels of psychological distress. Furthermore, it was demonstrated that this association was partially mediated by emotion regulation deficits. The findings emphasise the long-lasting impact of early family interactions on adult emotional well-being, suggesting that experiences of blame from caregivers may result in the internalisation of maladaptive emotional schemas that persist into adulthood. The PPBS thus offers a novel and reliable instrument for future research and clinical assessment of familybased emotional dynamics. The results of the study provide valuable implications for prevention and intervention programs aiming to strengthen emotion regulation skills and address maladaptive parental patterns within family and systemic therapy contexts.
Keywords: perceived parental blame; emotion regulation; adult psychological distress; attachment theory; family dynamics; scale development